Fifth Five Year Plan Draft Annual Plan 1974-75 Volume III Additional and inescapable requirements. Government of Bihar - Planning Commission (Planning Commission, 1973)
The Working Group has recommend an allocation of 18.80 crore for to annual plan of 1974-75. Projects with in allocation been included in volumes 1 and 2 of annual plan 1974-75. limited allocation is very inadequate particularly in some important sectors like 1-ower, Irrigation, Industries. Agriculture and Roads. It is not further augmented most of the continuing schemes will get delayed and in case of any new schemes, adequate headway can not be made during 1974-75.
Planning Department